2021
DOI: 10.1016/j.isci.2021.103034
|View full text |Cite
|
Sign up to set email alerts
|

Molecular competition can shape enhancer activity in the Drosophila embryo

Abstract: Live tracking of transcription reveals competition between transgenic reporters Transgenic reporters can also depress the expression of a neighboring gene Expression inhibition is in part because of competition for transcription factors (TFs)Competition is predicted with a model that restricts TFs to sub-nuclear ''hubs''

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 75 publications
1
8
0
Order By: Relevance
“…We acknowledge that thousands of genes are being transcribed in early embryos, and it is not intuitive to think that one additional transgene can affect the overall balance of TFs, Pol II, and PICs in each nucleus. Yet, others have reported similar phenomena of allelic competition, and we have also demonstrated that endogenous snail alleles interfere with each other ( Figure 4 ) ( Waymack et al, 2020 , 2021 ). While strong physical interactions between an enhancer and the target promoter often result in high transcriptional activity ( Symmons et al, 2016 ; Oudelaar et al, 2019 ), it was also demonstrated that the transcriptional efficiency is not linearly correlated with the degree of physical interactions ( Zuin et al, 2022 ).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…We acknowledge that thousands of genes are being transcribed in early embryos, and it is not intuitive to think that one additional transgene can affect the overall balance of TFs, Pol II, and PICs in each nucleus. Yet, others have reported similar phenomena of allelic competition, and we have also demonstrated that endogenous snail alleles interfere with each other ( Figure 4 ) ( Waymack et al, 2020 , 2021 ). While strong physical interactions between an enhancer and the target promoter often result in high transcriptional activity ( Symmons et al, 2016 ; Oudelaar et al, 2019 ), it was also demonstrated that the transcriptional efficiency is not linearly correlated with the degree of physical interactions ( Zuin et al, 2022 ).…”
Section: Discussionsupporting
confidence: 84%
“…One possible explanation is that transcription factors that are available to bind to enhancers are limiting. A recent study showed that a limiting number of transcription factors could lead to reduced RNA production from the homozygous allele ( Waymack et al, 2021 ). To further test this idea, we varied the strength of enhancer-promoter interactions without changing the enhancer sequence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, promoter competition might involve non-structural mechanisms whereby multiple promoters compete for rate-limiting factors (e.g. TFs, GTFs, RNA Pol2) present within shared transcriptional hubs 42,43,73 .…”
Section: Discussionmentioning
confidence: 99%
“…Instead, promoter competition might involve non-structural mechanisms whereby multiple promoters compete for rate-limiting factors (e.g. TFs, GTFs, RNA Pol2) present within shared transcriptional hubs 42,43,73 . Although these models and the putative rate-limiting factors await experimental validation, we speculate that nearby promoters with strong enhancer responsiveness and similar architecture (e.g.…”
Section: Discussionmentioning
confidence: 99%